Impact of first and second/third wave of COVID-19 pandemic on post-acute cardiovascular outcomes in Lombardy - Ojeda-Fernández, Luisa; Baviera, Marta; Foresta, Andreana; Tettamanti, Mauro; Zambon, Antonella; Macaluso, Giulia; Schena, Simone; Leoni, Olivia; Fortino, Ida; Roncaglioni, Maria Carla; Parati, Gianfranco (Frontiers in Cardiovascular Medicine, 2023)
Background: COVID-19 has been associated with a higher risk of post-acute complications. Our aim was to analyze and compare post-acute cardiovascular complications of COVID-19 survivors of the first and second/third pandemic waves in Lombardy, in both hospitalized and non-hospitalized COVID-19 patients.We included adults aged >40 years infected during the first and second/third waves of COVID-19 pandemic. The follow-up initiated 30 days after COVID-19 diagnosis and continued up to 9 months. Hazard ratios (HRs) and 95% Confidence intervals (CIs) of the post-acute cardiovascular outcomes were calculated against an inverse probability treatment weighted control group. Subgroup analysis were performed by age classes, sex, previous cardiovascular disease and stratified by COVID-19 hospitalization status to explore the impact of COVID-19 severity on outcomes. Compared to the control group, COVID-19 patients had an increased risk of hospitalization for any cardiovascular complications (HR 1 st wave 1.53 95% CI 1.38-1.69; HR 2 nd /3 rd wave 1.25 95% CI 1.19-1.31) and for individual cardiovascular outcomes, although HRs were higher in COVID-19 group from the 1 st pandemic wave. The results were confirmed in the subgroup analyses. Of note, the risk for any cardiovascular disease was also evident even among individuals who were not hospitalized during the acute phase of the infection.Our results provide evidence that COVID-19 is a risk factor for post-acute cardiovascular complications among different pandemic waves regardless of COVID-19 severity, age, sex and a history of cardiovascular diseases. Care strategies of people with COVID-19 should include cardiac monitoring.